267 Retrospective study evaluating the role of transvaginal ultrasound guided biopsy in gynecological cancer patients. (18th September 2019) - Mascilini, F; Testa, AC; Quagliozzi, L; Moro, F; Moruzzi, MC; Paris, V; De Blasis, I; Scambia, G; Fagotti, A
Abstract : Objectives: To evaluate the adequacy, safety and diagnostic accuracy of transvaginal ultrasound-guided biopsy. Methods: This is a retrospective study including patients with suspicious pelvic advanced tumors, primary (excluding cervical and vaginal cancer) or recurrent disease, or uncertain lesions who underwent transvaginal ultrasound guided biopsy at the Division of Gynaecologic Oncology, between April 2015 to May 2018. Transvaginal biopsies were performed with a 18-G/25 cm core-cut biopsy needle and finally histology was obtained. Results: A total of 63 women were analyzed. An adequate sample for histological analysis was obtained in all (100%) cases. Three patients (4.7%) complained for pain during the procedure, which was controlled by oral analgesic therapy and lasted for 10 min. No early and late complications were registered. Histopathological examinations showed 24/63 (38%) benign lesions (e.g fibrosis, inflammation, uterine or ovarian myoma) and 39/63 (62%) malignant tumors, distributed as follows: 35/39 (89.8%) malignant gynecological lesions, and 4/39 (10.2%) non gynecological malignant tumors. Among the malignant lesions, there were 15/39 (38.4%) primary tumors and 24/39 (61.6%) recurrent tumors. Thirteen patients underwent surgical treatment. Final histology was not in agreement with the results from tru-cut biopsy in 3 of 13 patients (23%); in particular benign disease at tru-cut biopsy resulted positive for malignancy at final histology (2 cases of recurrent cervical cancer and 1 case of recurrent vaginal cancer). Conclusions: Transvaginal ultrasound-guided tru-cut biopsy is an efficient, minimally invasive, accurate and safe diagnostic method for the management of pelvic tumors or uncertain lesions, where unnecessary surgery can be avoided in 80% of the cases.